Bourneville tuberous sclerosis - a case report - Mihaela Lungu; Alina Ursoiu; Mihaela Lefter (Romanian Journal of Neurology, 2013)
The diagnosis of Bourneville Tuberous Sclerosis – the ”forme fruste” – was established for a sixteen years old teenager, due to some typical cutaneous lesions, of angiofi bromas type, which appeared at puberty, lesions suggestive for the diagnosis. The imagery investigations confirmed the existence of brain hamartomas and angiomyolipomas of the kidneys, supporting the diagnosis of Bourneville disease.